Genetically encoded system to track histone modification in vivo - Sato, Yuko; Mukai, Masanori; Ueda, Jun; Muraki, Michiko; Stasevich, Timothy J.; Horikoshi, Naoki; Kujirai, Tomoya; Kita, Hiroaki; Kimura, Taisuke; Hira, Seiji; Okada, Yasushi; Hayashi-Takanaka, Yoko; et al. (Scientific reports, 2013)
Post-translational histone modifications play key roles in gene regulation, development and differentiation, but their dynamics in living organisms remain almost completely unknown. To address this problem, we developed a genetically encoded system for tracking histone modifications by generating fluorescent m odification-specific int racellular anti bodies (mintbodies) that can be expressed in vivo . To demonstrate, an H3 lysine 9 acetylation specific mintbody (H3K9ac-mintbody) was engineered and stably expressed in human cells. In good agreement with the localization of its target acetylation, H3K9ac-mintbody was enriched in euchromatin and its kinetics measurably changed upon treatment with a histone deacetylase inhibitor. We also generated transgenic fruit fly and zebrafish stably expressing H3K9ac-mintbody for in vivo tracking. Dramatic changes in H3K9ac-mintbody localization during Drosophila embryogenesis could highlight enhanced acetylation at the start of zygotic transcription around mitotic cycle 7. Together, this work demonstrates the broad potential of mintbody and lays the foundation for epigenetic analysis in vivo .